KONFLIK PERAN DAN AMBIGUITAS PERAN SEBAGAI PREDIKTOR KINERJA KARYAWAN PADA BPR DI KABUPATEN GIANYAR - Yunita, Putu Irma; Astawa, Putu Rosa Wijayanti (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
The purpose of this research is to examine the influence of role conflict which consists of work family conflict and family work conflict and role ambiguity on performance of BPR employee's in Gianyar Regency. This research also examined the moderating effect of gender on the relationship of work family conflict, family work conflict, and role ambiguity on employee performance. Data collection techniques in this study used a questionnaire that had been tested for validity and reliability first. The population in this study were 5 BPR of 25 BPR on Gianyar Regency. The method of determining the sample uses the criteria of married employees, so that the sample in this study was 110 women and 70 men. The WrapPLS version 6.0 analysis method is used to test the proposed hypothesis. The results showed that work family conflict, family work conflict, and role ambiguity had a negative and significant influence on employee performance. However, gender does not have a moderating effect on the relationship between work family conflict, familywork conflict, and roleambiguity on employee performance.